Cultural Dynamics Shaping the Adoption of Modern Management, Green Innovation, and Digitization in Uzbekistan's Business Landscape: Dinamika Budaya Membentuk Adopsi Manajemen Modern, Inovasi Hijau, dan Digitalisasi di Lanskap Bisnis Uzbekistan - Ogunmola, Gabriel Ayodeji (Academia Open, 2024)
Since the gain of independence in 1991, Uzbekistan has worked through diverse economic transformations with a transition from a central economy to a Market economy. These have sought to develop entrepreneurship and encourage FDI inflows, at the same time business is still shaped by history, culture and institutions. For this investigation, the affect of the cultural dimensions including collectivism, power distance, and long term orientation towards the adoption of modern management practices, green innovation and digitization in Uzbekistan is examined. Hofstede’s Cultural Dimensions Theory, Theory of Planned Behavior, and the Technology-Organization-Environment are used to analyze these influences in the present research. The study shows that collectivism positively influences the implementation of the modern management practices while high power distance negatively influence it. Long-term orientation to a very large extent influences green innovation and appropriate attitude toward technology is essential for digitalization. Subjective norms which are highly endorsed scale and perceived behavioral control further enhance green innovation and digitization respectively. Furthermore, other adoption conditions such as the technological and environmental support for the adoptions are important while size and centralization of organizations present adoption challenges. Thus, this work enriches the scientific literature by revealing the dependencies of business activities in a transitional economy with respect to cultural values. The conclusions for business and authorities stress the importance of cultural contingency approach to improve organization performance and improvement in Uzbekistan. The future research should incorporate longitudinal studies and pay attention to such other cultural dimensions and characteristics of organizations. Highlights: Uzbekistan transitions from central to market economy, shaping business by culture. Collectivism aids modern management; power distance hinders; long-term orientation boosts innovation. Cultural values, technology, and environment critical for green innovation, digitization success. Keywords: Cultural dimensions, Hofstede's Cultural Dimensions Theory, Theory of Planned Behavior, Technology-Organization-Environment framework, sustainability